Wendt India Limited - Bathini, Dharma Raju; Vohra, Neharika, 1966-; Jaiswal, Manoj (London : Indian Institute of Management, Ahmedabad, 2015)
Consistent growth and profitability had been the bedrock of Wendt India Limited (WIL) over the past ten years, in spite of huge financial mismanagement in the initial years and three ownership changes at group level. The strategic intent of WIL, "to become a significant global player in offering customized functionally superior products/services for grinding and machining hard-to-process material," kept the leaders of the company focused on exceptional performance. Despite a remarkable track record, WIL posted a lower growth 3.1% (CAGR) during 2007-2010, against an impressive 18% (CAGR) during 2000-2007. Rajesh Khanna, Chief Executive Officer of WIL, knew that the company's growth was tied to the perceptible slowdown in the economy post 2007. Industry analysts speculated that over the next few years, the abrasive industry itself was expected to grow at 7.2% per annum, mirroring the GDP growth rate. Goaded by the group chairperson's expectation that each business within the Murugappa group had to grow at three times the country's GDP growth rate, and personal belief that slowing down was not an option, Rajesh had set aggressive targets. He knew he would have to provide direction on how to reach the set expectations. He needed a coherent and strategic action plan.
Originally published in Bathini, D. R., Vohra, N., & Jaiswal, M. (2015). Wendt India Limited. OB0219. Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Khanna, Rajesh, -- active 2015.; Wendt India Limited; Murugappa Group; Corporations -- Growth